P570 Kock pouches in the 21st century: a descriptive study of short-term (30-day) outcomes in a national cohort of 177 patients. (25th January 2019) - Shawki, S; Steele, S; Lipman, J; Lee, C H A; Stocchi, L; Hull, T; Gorgun, E; Holubar, S
Abstract: Background: In 1972, Professor Nils Kock in Gothenburg Sweden developed the continent ileostomy (Koch pouch or KP) as an alternative to permanent end ileostomy. However, the KP was largely supplanted by the ileal pouch-anal anastomosis (IPAA). In the 21st century, KP's are rarely performed, and often only in highly select patients who are a not candidate for an IPAA. Presently, there are only single institution case series with which to guide surgeons' and patients' expectations for postoperative outcomes including length of stay, readmission and complication rates. Thus we aimed to report surgical outcomes in a large national retrospective cohort using the National Surgical Quality Improvement Project (NSQIP). Methods: Using the NSQIP Participant User File from 2005–2017 we identified patients who underwent a KP (CPT 44386). Baseline characteristics, operative variables, and postoperative outcomes are reported. Figures represent frequency (proportion) or median (interquartile range). Results: Over an 11-year period, a total of 907146 colorectal operations were performed; of these, we identified a sample of 177 patients who underwent Kock pouch procedures. The median age was 56 (46–76), 50.2% were women, and the median body mass index was 25.3 (22–29.6) kg/m 2 . Any comorbidity was present in 105 (59%), with a median of 1 (0 – 2) comorbidities. A total of 13 (7.3%) and 16 (8.5%) were on steroids or had recent weight loss, respectively, and the median albumin was 3.8 (2.9–4.1) mg/dl. Most patients were ASA class 2 (78, 44%). Operative time was 198 (129.5–298.5) min, and 127 (72%) had other procedures by the same surgical team, while only 24 (14%) had concurrent procedures by a different surgical team. In terms of short-term outcomes, reoperation was required in 19 (10%) of patients, the post-operative length of stay was 8 (5–14) days. Readmission occurred in 14 (7.9%) of patients. VTE occurred in 4 patients (2.3%). Overall any complication of any severity occurred in 67 (38%) patients. The 30-day mortality rate was 3.4% (6 patients). Conclusions: The Kock pouch procedure, despite its technical complexity, has an acceptable short-term safety profile, and remains an option for a selective group of motivated patients who cannot have IPAA and/or defer end ileostomy.